MINIMALLY INVASIVE GLAUCOMA SURGERY (MIGS): COMPARISON OF TRABECULAR VERSUS SUPRACHOROIDAL ROUTE - Ridho Ranovian; Widya Artini Sumantri (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Because of the high rate of complications associated with traditional glaucoma filtering surgery, various research were launched to develop a new device, such as drainage channels, such as Glaucoma Drainage Devices. Objective: To compare the efficacy and safety of trabecular route and suprachoroidal MIGS in eyes with mild to moderate glaucoma with and without cataract extraction of these two devices. Methods: Literature search was conducted using online database such as Google Scholar, Pubmed, Survey of Ophtalmology, and Clinical Key. Result: Since the IOP-lowering efficacy of these treatments is restricted by episcleral venous pressure, MIGS targeting the trabecular outflow system may be the best option for patients with mild-to-moderate open-angle glaucoma. Conclusion: The implantation of trabecular iStents resulted in a considerable reduction in IOP, particularly in mild and moderate POAG. Both MIGS versions have good efficacy and safety profiles, with only minor problems like microscopic hyphema and stent blockage. Keywords: glaucoma, Minimally Invasive Glaucoma Surgery (MIGS), iStents, cypass